Antioxidation and anti-inflammatory actions of the extract of Nitraria Tangutorum Bobr. fruits reduce the severity of ulcerative colitis in a dextran sulphate sodium-induced mice model. (April 2022) - Zou, Qiuping; Feng, Jian; Li, Ting; Cheng, Guiguang; Wang, Weiguang; Rao, Gaoxiong; He, Hongping; Li, Yanping
Graphical abstract: Highlights: 25 compounds were characterized from the extracted of Nitraria Tangutorum Bobr. fruits by using UHPLC-ESI-HRMS/MS method. All extracts exhibited antioxidant activity and enhanced the activities of antioxidant enzymes in HepG-2 cells. CE presented the highest phenolics, and has the best antioxidant and anti-inflammatory effects in vivo and in vitro. CE reduced weight loss and the disease activity in DSS-induced UC mice. CE inhibited the activation of MAPK/NF- κ B signaling pathways. Abstract: In the present study, we characterised 25 compounds in the extract of Nitraria Tangutorum Bobr. fruits by using the HPLC/MS/MS method. We determined the antioxidant activities of ethanol, petroleum ether, chloroform (CE), ethyl acetate, n-butanol, and water extracts of N. Tangutorum fruits. All extracts were found to exhibit the antioxidant activity and significantly enhance the activities of antioxidant enzymes in H2 O2 -induced HepG-2 cells. Furthermore, the anti-inflammatory effect and molecular mechanism of the CE of N. Tangutorum Bobr. fruits were evaluated using the dextran sulphate sodium (DSS)-induced ulcerative colitis (UC) mouse model. CE significantly restored the body weight reduction, colon shortening, DAI elevation, and histological score in DSS-induced UC mice ( P  < 0.01). In addition, CE could remarkably decrease the levels of MPO, IL-1 β, TNF- α, and IL-6 and increase the levels of superoxide dismutase, catalase, glutathione, and IL-10 in the colon of DSS mice ( P  < 0.01). According to western blot analysis, CE inhibited the MAPK/NF- κ B signalling pathway activation. The results indicated that CE exerts a protective effect on DSS-induced UC mice, which may be related to the MAPK/NF- κ B signalling pathway activation. In conclusion, CE can be used as a therapeutic drug for UC.